2021
DOI: 10.1111/php.13526
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Modulated by Red/NIR Light: Phagocytosis, Cytokines, Mitochondrial Activity, Ca2+ Influx, Membrane Depolarization and Viability

Abstract: Low-level light therapy (LLLT) is emerging as a promising therapeutic approach to modulate the biochemical and molecular processes within living cells. LLLT is known to produce local and systemic effects; therefore, immune cells in local tissues or in the circulation are affected by light. However, this specific effect remains weakly explored. In this study, the effect of red (650 nm) and NIR (808 nm) light on phagocytosis (respiratory burst), cytokine expression, mitochondrial activity, ROS generation, Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
(116 reference statements)
1
6
0
Order By: Relevance
“…HeLa and 4T1 cancer cells show slow linear-like rising dynamics of ROS generation, but the ROS level after 10 min becomes higher than in other cells: by 38 and 26% in HeLa cells and by 39 and 30% in 4T1 cells under 650 and 808 nm light, respectively. In our experiments, comparing red and NIR light at the same intensity, it can be argued that light of 650 nm wavelength more efficiently stimulates mitochondrial ETC and subsequent ROS generation than 808 nm, which is consistent with literature data (3,4,28,58).…”
Section: Light-induced Ros Generation In Different Cell Linessupporting
confidence: 92%
See 2 more Smart Citations
“…HeLa and 4T1 cancer cells show slow linear-like rising dynamics of ROS generation, but the ROS level after 10 min becomes higher than in other cells: by 38 and 26% in HeLa cells and by 39 and 30% in 4T1 cells under 650 and 808 nm light, respectively. In our experiments, comparing red and NIR light at the same intensity, it can be argued that light of 650 nm wavelength more efficiently stimulates mitochondrial ETC and subsequent ROS generation than 808 nm, which is consistent with literature data (3,4,28,58).…”
Section: Light-induced Ros Generation In Different Cell Linessupporting
confidence: 92%
“…Figure 1 shows the effect of light of 375/450/530/650/808/1064 nm wavelengths at various power densities from 10 to 300 mW cm À2 (for 1064 nm light from 0.1 to 2 W cm À2 ) on ROS generation in the neuroblastoma model. These light power densities and doses have been chosen because red/NIR PBM with commonly used parameters (10-100 mW cm À2 , ~0.1-30 J cm À2 ) provides positive effects on tissues and cells without inhibiting their viability, while light at power densities higher than 100 mW cm À2 and doses higher than ~10 J cm À2 may be unsafe for tissue cells causing nonthermal cell phototoxicity (3,4,28,(48)(49)(50)(51)(52)(53)(54). So, we investigate the influence of so-called low-intensity light below 100 mW cm À2 and irradiation with higher intensities above this edge, in which neither causes heating.…”
Section: Light-induced Ros Generation In Neuroblastoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study further confirmed the anti-inflammatory effect of PBM on macrophages collected from male mice with reduced pro-inflammatory cytokines and increased anti-inflammatory cytokines. Interestingly, the biphasic dose-response was observed in cell viability, which was increased at a lower dosage but decreased at a higher dosage [ 105 ].…”
Section: Pbm Overviewmentioning
confidence: 99%
“…There is limited evidence that longer wavelength exposure also impacts on immunity [11][12][13] . However, this remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%